PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DENGAN TEKNIK PROBING UNTUK MENINGKATKAN PENGUASAAN KONSEP SISWA PADA MATERI SUHU DAN KALOR DI SMP - Zulpiana Zulpiana; Azhar Azhar; Naila Fauza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The aim of the study was to describe the students' mastery of the concepts in class VII Islamic Middle School of Fullness by applying the Numbered Head Together (NHT) learning model with the Probing technique. The design used is Quasi Experiment: Posttest only control group design. The population in this study were all students of class VII KeFullan Islamic Middle School for the 2022/2023 Academic Year with a sample of 38 students consisting of class VII-A as the control class, totaling 19 students and class VII-B as the experimental class, totaling 19 students. student. The data collection instrument was a mastery test on the concept of temperature and heat, which consisted of 12 multiple choice questions which were tested for validity with a supervisor. The data analysis technique used was descriptive analysis through the average value of students' mastery of concepts and inferential analysis through normality tests, homogeneity tests and hypothesis tests with the help of the SPSS 23 program. The results showed that learning increased as seen from the average mastery score Students' concepts in the experimental class applying Numbered Head Together (NHT) learning with the Probing technique have a score of 74.55% higher than the control class applying conventional learning a score of 63.59% and there is a significant difference in students' mastery of concepts between the experimental class and the control class .Keywords: Concept Mastery, Numbered Head Together (NHT) with Probing techniques.